1980
DOI: 10.1126/science.7434029
|View full text |Cite
|
Sign up to set email alerts
|

Human Sleep: Its Duration and Organization Depend on Its Circadian Phase

Abstract: Two- to threefold variations in sleep length were observed in 12 subjects living on self-selected schedules in an environment free of time cues. The duration of polygraphically recorded sleep episodes was highly correlated with the circadian phase of the body temperature rhythm at bedtime and not with the length of prior wakefulness. Furthermore, the rate of REM (rapid eye movement) sleep accumulation , REM latency, bedtime selection, and self-rated alertness assessments were also correlated with the body temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
298
2
13

Year Published

1981
1981
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 816 publications
(329 citation statements)
references
References 11 publications
16
298
2
13
Order By: Relevance
“…Under these circumstances, PS propensity increases shortly after the circadian minimum of CBT (12), a feature that is present also in spontaneously desynchronized human subjects (17,19). The robust Ͼ24 h oscillation of CBT in the present study hinted to the possibility that this tight correlation between CBT circadian rhythmicity and PS may also be present in the forced desynchronized rat.…”
Section: Resultssupporting
confidence: 48%
See 1 more Smart Citation
“…Under these circumstances, PS propensity increases shortly after the circadian minimum of CBT (12), a feature that is present also in spontaneously desynchronized human subjects (17,19). The robust Ͼ24 h oscillation of CBT in the present study hinted to the possibility that this tight correlation between CBT circadian rhythmicity and PS may also be present in the forced desynchronized rat.…”
Section: Resultssupporting
confidence: 48%
“…Although humans do not exhibit two rhythms of rest-activity as our rats do, this may be a consequence of the experimenter-imposed forced rest-activity cycle. Notably, human subjects under spontaneous internal desynchronization do show evidence of two rest-activity periodicities, one that freeruns with a much longer than 24-h period and another that is in phase with the circa 24-h rhythm in CBT (17,18).…”
Section: Resultsmentioning
confidence: 99%
“…2 makes it clear that, as with older individuals, the sleep of these younger subjects was differentially affected in the second half of night. The dramatic rise in wakefulness during the last two hours of sleep reflects the difficulties associated with maintaining sleep on the rising portion of the temperature curve (Czeisler et al 1980;Akerstedt and Gillberg 1981;Gillberg and Akerstedt 1982;Akerstedt 1988;Dawson and Campbell 1991). In an earlier study using morning bright light exposure, Dijk and co-workers (Dijk et al 1987) reported similar results, though in a different context.…”
Section: Discussionmentioning
confidence: 99%
“…The direct soporific effects of melatonin on nighttime sleep in normal subjects have been described as modest (e.g., . The advantage of using the phase-shifting properties of melatonin to treat non-24-h sleep-wake disorder is based on the fact that sleep quality and quantity are maximal if sleep occurs at the optimal circadian phase (Czeisler et al, 1980;Dijk and Czeisler, 1994), and it appears that even a small degree of desynchrony may result in insomnia symptoms (Morris et al, 1990). Recent evidence in the blind suggests that if the circadian system continues to free run during melatonin treatment, the sleep-wake cycle also continues to free run, despite the acute sleep-improving effects of melatonin (Lockley et al, unpublished results), and thus the underlying cause of the sleep disorder remains untreated.…”
Section: Discussionmentioning
confidence: 99%